Determinants of stock market return in retail industry (Parkson Holdings Berhad) / Nur Liyana Abu Shah and Nur Elisa Shaharullah - Abu Shah, Nur Liyana; Shaharullah, Nur Elisa (Faculty of Business and Management, 2019)
The study has been conducted to determine whether the macroeconomics variables give impact towards stock market returns of Parkson Holding Berhad (PHB) in Malaysia from 2004 to 2017 which contains quarterly data set of 56 observations. The primary objective of this research is to investigate the relationship between macroeconomic variables which are Inflation (INF), Exchange Rate (EXC), Crude Oil Price, Interest Rate (INT) and Gross Domestic Product (GDP) with stock market return of Parkson Holdings Berhad (PHB). The relationship between independent variables (INF, EXC, COP, INT and GDP) and dependent variable (PHB). This paper employs Ordinary Least Square (OLS) to determine the statistical relationship. For the diagnostic checking, there are no heteroscedasticity, no autocorrelation, no model specification problem, no multicollinearity and normally distributed. In conclusion, according to the result that use compounded return to convert all of the raw data form, it reveals that EXC, INT and GDP are significant to stock market return of PHB at the significant level of 0.01 and 0.05. Meanwhile, INF and COP are insignificant to stock market return of PHB due to value of probability exceeded the significant level of 0.10.